Prevalence and risk factors for recurrent Ischemic stroke at two tertiary hospitals in Kuantan - Ismail, Rasimah; Ayub, Adibah; Basiam, Sulaila (Universiti Kebangsaan Malaysia (UKM), 2023)
Introduction: Recurrent strokes are rising globally, especially in Malaysia, and is a major cause of morbidity and mortality. This study examines the prevalence and risk factors of recurrent ischemic stroke in two tertiary hospitals in Kuantan. Materials and Methodss: This study is a cross-sectional retrospective study which was conducted on ischemic stroke patients who attended two tertiary hospitals in Kuantan in 2022. Results: This study included 532 individuals, 380 with first episode of stroke and 152 with recurrent ischemic stroke. The prevalence of recurrent ischemic stroke is 28.6%. The mean age of recurrent ischemic stroke is 63.33 years and male gender and Malay ethnicity are more predominant. Risk factors that show significant positive association are hypertension (p < 0.001, OR 29.940, 95% CI 9.937-90.208), diabetes mellitus (p < 0.001, OR 11.089, 95% CI 4.181- 29.409), hyperlipidaemia (p < 0.001, OR 3.457, 95% CI 1.924-6.209) and ischemic heart disease (p < 0.001, OR 3.102, 95% CI 1.758-5.472). Our study did not reveal any significant correlations between age, gender, race, smoking, family history of stroke, HbA1c level, BMI categories, and compliance to medications with regards to recurrent ischemic stroke. We also examined stroke subtypes and severity in recurrent stroke patients using the Oxfordshire Community Stroke Classification (OCSP) classification and National Institute of Health Stroke Scale (NIHSS) score. Most common stroke subtypes are LACI and PACI. TACI is associated with age, atrial fibrillation and ischemic heart disease. Most patients had moderate stroke. Stroke severity is also associated with age, smoking, ischemic heart disease and atrial fibrillation. Conclusion: Our study found a high prevalence of recurrent ischemic stroke and associated risk factors includes hypertension, diabetes mellitus, hyperlipidaemia and ischemic heart disease. Therefore, it is critical to recognize and control these risk factors to reduce the likelihood of recurrent ischemic stroke, and thus reducing morbidity and mortality.